Identifying Risk Factors of Boot Procurement: A Case Study of Stadium Australia (Construction Economics and Building, 2012)
Private sector input into the procurement of public works and services is continuing to increase. This has partly arisen out of a requirement for infrastructure development to be undertaken at a rate that maintains and allows growth. This has become a major challange for the construction industry that cannot be met by government alone. The emergence of Build-Own-Operate-Transfer (BOOT) schemes as a response to this challange provides a means for developing the infrastructure of a country without directly impacting on the governments budgetary constraints. The concepts of BOOT are without doubt extremely complex arrangements, which bring to the construction sector risks not experienced previously. Many of the infrastructure partnerships between public and private sector in the pastare yet to provide evidence of successful completion, since few of the concession periods have expired. This paper provides an identified list of risk factors to a case study of Stadium Australia. The most significant risk associated with Stadium Australia include the bidding process, the high level of public scrutiny, post-Olympic Games facility revenue and the complicated nature of the consortium structure.